2019
DOI: 10.1177/0825859719868174
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Costs of Health Care in a Kidney Supportive Care Program

Abstract: Kidney supportive care (KSC) is a patient-centered model of multidisciplinary care designed for patients with advanced chronic kidney disease (CKD) and end-stage kidney disease (ESKD). Our goal was to characterize the types, frequencies, and costs of services accessed by patients enrolled in a KSC program. We analyzed health care utilization data prospectively collected from 102 patients who enrolled in the KSC program during the first 52 weeks of its existence. The data comprised program appointments, emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We did not identify any study reporting the prevalence of functional diarrhea in CKD. Studies reporting self-reported diarrhea were conducted primarily in the WHO Western Pacific (7 studies [ 24 , 35 , 37 , 42 , 58 , 64 , 67 ]) and European (6 studies [ 30 , 31 , 38 , 53 , 62 , 65 ]) Regions, whereas only one study each was conducted in the African (Nigeria [ 43 ]) and Eastern Mediterranean (Saudi Arabia [ 68 ]) Regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not identify any study reporting the prevalence of functional diarrhea in CKD. Studies reporting self-reported diarrhea were conducted primarily in the WHO Western Pacific (7 studies [ 24 , 35 , 37 , 42 , 58 , 64 , 67 ]) and European (6 studies [ 30 , 31 , 38 , 53 , 62 , 65 ]) Regions, whereas only one study each was conducted in the African (Nigeria [ 43 ]) and Eastern Mediterranean (Saudi Arabia [ 68 ]) Regions.…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected using authors’ questionnaires/during anamnesis in the case of 4 studies [ 30 , 42 , 43 , 66 ], and using validated questionnaires: the POS-S Renal questionnaire and its modifications/translations in 6 studies [ 24 , 27 , 31 , 35 , 64 , 65 ]; IPOS-Renal in 3 studies [ 37 , 39 , 67 ]; DSI in 3 studies [ 53 , 57 , 58 ]; MSAS-SF questionnaire in 2 studies [ 44 , 62 ]; CKD Symptom Index—Sri Lanka (CKDSI-Sri Lanka) in 2 studies [ 34 , 36 ]; and CKD Symptom Burden Index (CKD-SBI [ 68 ]) and Renal Disease Questionnaire (RDQ [ 38 ]) in one study each.…”
Section: Resultsmentioning
confidence: 99%
“…The medical staff interviewed in this study indicated that they supported the value of KSC in the palliative treatment of kidney diseases, but also suggested that the development of KSC in mainland China is facing a big dilemma.The development of KSC in China needs to be actively explored in combination with China's cultural background. First of all, public education should be strengthened to improve the public's understanding and support for palliative care.The establishment of specialized palliative care teams in the eld of renal diseases, and the establishment of organizational frameworks at different levels from the hospital to the community.Use professional team building to promote public education and encourage patients and family members to participate in discussions and learn about KSC [34] .To give full play to the guiding role of policies [35] , government departments need to formulate policies to promote the development of palliative care and improve the quality of old-age care services.To clarify the division of responsibilities among government, society and family, and provide policy support for the development of specialized palliative care of kidney disease.Secondly,we should fully integrate KSC with our traditional culture, actively investigate the needs of Chinese kidney patients for KSC, and determine the best mode of application of KSC in our clinical practice, so as to meet the needs of patients and their families to the greatest extent [36] .Finally, international cooperation should be strengthened to further determine the development path of palliative medicine in end-stage renal diseases, optimize the admission criteria and implementation content of KSC, and reach international consensus on the application of KSC, so as to promote the consistency of clinical practice, research and policy.…”
Section: Discussionmentioning
confidence: 99%
“…87 Although only 1 study met the criteria for inclusion in this review, we reviewed many articles describing palliative care for kidney disease in the United States and abroad. 51,[88][89][90] Results are promising, with reduced ED utilization demonstrated following the initiation of palliative care plans for kidney failure patients who decline dialysis. 88 The high mortality of maintenance HD and the paucity of transplants makes establishing end-oflife goals of care an important consideration for all HD patients.…”
Section: Discussionmentioning
confidence: 99%